Intraspecific Trait Variation in Seedlings Reveals Independence Between Leaf and Root Traits but a Lack of an Independent “Collaboration Axis” Belowground - Samuel A. Z. Schaffer‐Morrison; Inés Ibáñez; Monique Weemstra; Lais Petri; María Natalia Umaña (Plant-Environment Interactions)
ABSTRACT Plant functional traits help determine resource acquisition strategies. Global trends at the interspecific scale suggest independence between leaf and root traits described by three functional dimensions: resource acquisition above‐ and belowground and degree of mycorrhizal collaboration belowground. However, there are ecological and evolutionary reasons to expect different patterns of variation within species, especially within seedlings—the stage at which most tree mortality occurs. Describing the intraspecific patterns of trait variation in seedlings will improve the understanding of tree populations' ability to cope with environmental change. We ask the following questions: (1) How do traits above‐ and belowground co‐vary within species? (2) How do traits relate to soil nutrients and light conditions? We collected root and leaf traits on 131 seedlings from four naturally occurring woody species across eight sites in a temperate, deciduous broadleaf forest in the USA. We measured traits reflecting resource use strategies—specific leaf area, leaf nitrogen, root nitrogen, and root tissue density—and those defining the collaboration axis—specific root length and root diameter. We measured light conditions for each seedling and soil nitrogen and phosphorus to examine the relationship between traits and abiotic conditions using a novel multivariate regression analysis approach. We found that above‐ and belowground traits segregated into independent functional axes and that the collaboration axis merged with the belowground resource‐acquisition axis. We found limited associations between abiotic factors and traits. Our findings suggest that within species, there might be additional constraints to adjust to soil conditions and therefore impact response to environmental change.